Exploring Educational Software in Computing Education for Students with Autism Spectrum Disorder: A Systematic Mapping Study - Silva, Kennedy dos S.; C. Junior, Amaury Antônio de; Guedes, Leandro S.; Paiva, Debora Maria B. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
The growing inclusion of students with Autism Spectrum Disorder (ASD) in mainstream schooling requires adapted pedagogical approaches, especially in Computing. Educational software shows significant potential for developing computational thinking, but barriers in personalization and accessibility persist. This study presents a systematic mapping of 17 primary studies on educational software for teaching Computing to students with ASD. Our analysis reveals tools like visual programming and serious games focusing on fundamental skills, yet a lack of personalization and empirical validation remains. This mapping highlights critical research gaps and provides a structured overview to guide future development. We also classify the pedagogical strategies using Bloom’s Taxonomy and the Computational Thinking competencies using Brennan and Resnick’s framework to inform more inclusive solutions.